Gender and Poverty : A Life Cycle Approach to the Analysis of the Differences in Gender Outcomes - Lokshin, Michael; Mroz, Thomas A. (World Bank, Washington, DC, 2014)
The authors study complex interactions between gender and poverty in postwar Bosnia and Herzegovina. The goal of their analysis is to uncover how a spectrum of gender differentials at different parts of the life cycle varies across income groups. Using the data from the 2001 Bosnia and Herzegovina Living Standards Measurement Study, the authors find strong gender-poverty interaction in the patterns of labor force participation, gender gap in earnings, individuals' school finances, and school attendance. The main source of gender inequality seems to come from differences in investments in girls' and boys' educations that increase with declines in income levels. Short-term income shocks could lead to long-term increases in gender inequality in households with school age children, unless there is ready access to credit markets. The authors also find that the magnitude of the impact of economic development on gender differences in Bosnia will depend on where the growth is concentrated. If the poor capture at least some benefits of economic growth, the gender differences in household investment in human capital of their children will decline. If, on the other hand, growth is concentrated among the richest, then important gender disparities could remain pervasive.